2014
DOI: 10.1016/j.enpol.2014.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Owners of second homes, locals and their attitudes towards future rural wind farm

Abstract: Wind power has been identified as one of the most promising sources of renewable energy. However, its diffusion has not been as rapid as anticipated. The objective here is to analyse attitudes towards wind power among Finnish local residents and owners of second homes. First, we assess their existing knowledge of and level of interest in energy issues and wind power. Second, we analyse potential differences in attitudes between the two stakeholder groups when it comes to wind power in general and the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Operationalizing newcomer status this way ensures that residents who are considered long‐term are sufficiently integrated within their communities and that the time all residents, regardless of age, have spent in the community is regarded equally. Since prior research has shown that permanent and part‐time residents of rural areas have distinct viewpoints on community issues (e.g., Armstrong and Stedman ; Janhunen, Hujala, and Pätäri ), we also added a separate category for seasonal residents (part‐time resident = 2) in this measure. Part‐time residents simply responded on the survey that they lived part of the year somewhere else (no indication of how long).…”
Section: Methodsmentioning
confidence: 99%
“…Operationalizing newcomer status this way ensures that residents who are considered long‐term are sufficiently integrated within their communities and that the time all residents, regardless of age, have spent in the community is regarded equally. Since prior research has shown that permanent and part‐time residents of rural areas have distinct viewpoints on community issues (e.g., Armstrong and Stedman ; Janhunen, Hujala, and Pätäri ), we also added a separate category for seasonal residents (part‐time resident = 2) in this measure. Part‐time residents simply responded on the survey that they lived part of the year somewhere else (no indication of how long).…”
Section: Methodsmentioning
confidence: 99%
“…The significant correlation between the installed capacity of wind energy and the rate of urbanisation in Czech districts supports the hypothesis that wind farms are more likely to be implemented in areas with a lower concentration of second home or holiday home owners escaping from a city for unspoiled landscapes and the 'rural idyll ' (Cowell et al, 2011;Janhunen et al, 2014;van der Horst and Toke, 2010). An interesting finding from our analysis is the small but significant correlation between the higher installed capacity of wind energy and the location of a district in borderland areas.…”
Section: District Category 1 Statisticsmentioning
confidence: 67%
“…Most studies have been concerned with the local acceptance of wind energy projects (e.g. Jobert et al, 2007;Janhunen et al, 2014;Fast and Mabee, 2015;Firestone et al, 2015;Rand and Hoen, 2017). Research to date demonstrates the complex and multi-faceted dimensions of 'acceptance', as factors range from personal characteristics, perceived side-effects, process-related variables, and technical and geographical issues (Langer et al, 2016).…”
Section: Spatial Differentiation and The Uneven Development Of Renewamentioning
confidence: 99%
“…Incluímos un conxunto de cinco preguntas, unha primeira para coñecer o interese xeral por temas relacionados coa enerxía (Janhunen, Hujala e Pätäri, 2014), e catro cubrindo a motivación ambiental ou económica de aspectos concretos relacionados con esta: a preocupación polo cambio climático (Bauwens, 2016) e pola preservación e conservación da contorna natural (Fleiß et al, 2017), por unha banda, e o grao de preocupación sobre a evolución actual dos prezos da enerxía ou a escasa transpa-rencia e información en relación a como se determinan os ditos prezos (Bauwens, 2016), pola outra. As preguntas foron avaliadas utilizando unha escala tipo Likert de 1 "moi baixo" a 5 "moi alto".…”
Section:  Preocupación Por Temas Relacionados Coa Enerxíaunclassified